La democratización del libro: desde la piratería a los monopolios - Darnton, Robert (2021)
In this note, Robert Darnton, renowned culture and book historian, shares some reflections around the book invention and the historical evolution of its commercial circuits. By commenting the XVIIth and XVIIIth centuries book piracy and the recent attempts of platforms such as Google of creating open virtual libraries, Darnton brings up the debate surrounding the tension between the copyright and the democratization of reading by making books more accessible to everyone.